RADICAL OPERATIONS OF INGUINAL HERNIAS WITH THE TEMPORARY TRANSLOCATION OF INGUINAL NERVES - A. P. Tsitsura; A. I. Fetyukov (Вестник хирургии имени И.И. Грекова)
This article presents the results of anatomic researches of the innervations of the inguinal area, performed for studying an arrangement of the main nerves of the inguinal area in relation to the operation access and the area of plasty of the posterior wall of the inguinal canal. The method of temporary translocation of inguinal nerves is developed for their preservation at radical operations of inguinal hernias. Long-term experience of surgical treatment of inguinal hernias with the temporary translocation of inguinal nerves is summarized.